Numerical correction for the diffuse solar irradiance by the melo-escobedo shadowring measuring method - Dal Pai, Alexandre [UNESP]; Escobedo, João Francisco [UNESP]; Corrêa, Fábio Henrique Pires [UNESP] (My University, 2011)
The present paper deals with numerical corrections factors proposed as a function of the clearness index in order to correct the diffuse solar irradiance measured with the Melo-Escobedo Shadowring Measuring Method (ME shadowring). The global irradiance was measured by an Eppley - PSP pyranometer ; direct normal irradiance by an Eppley-NIP pyrheliometer fitted to a ST-3 sun tracking device and the diffuse irradiance by an Eppley-PSP pyranometer fitted to a ME shadowring. The validations were performed by the MBE and RMSE statistical indicators. The results showed that the numerical correction factors were appropriate to correct the shadowring diffuse irradiance.
Keywords: Clearness indices; Correction factors; Diffuse irradiance; Diffuse solar irradiance; Direct normal irradiances; Global irradiance; Measuring method; Pyranometers; Statistical indicators; Sun-tracking; Ion selective electrodes; Solar radiation; Numerical methods